Evidence for the Paleoethnobotany of the Neanderthal: A Review of the Literature - Gerhard P. Shipley; Kelly Kindscher (Scientifica, 2016)
Our perception of our closest human relatives, the Neanderthals, has evolved in the last few decades from brutish ape-men to intelligent archaic human peoples. Our understanding and appreciation of their cultural sophistication has only recently extended to their diet. Only within the last few years, with new techniques and a shift in focus, have we begun to truly investigate and understand the role of plants in their diet and culture. The more we learn about Neanderthals, the more we realize that biological and cultural distinctions between them and us were relatively small. Given that we coexisted and likely interacted with them for thousands of years, the more we learn about them, the better we may understand our own past. In that light, we review the current evidence, derived from such sources as plant remains (e.g., starch, pollen, phytoliths, and seeds) in soil and dental calculus, dental and tool wear, coprolites, and genetics, for Neanderthal’s nutritional, medicinal, and ritual use of plants, which includes 61 different taxa from 26 different plant families found at 17 different archaeological sites. Further, we updated and standardized botanical nomenclature from many sources published over many decades to provide a more stable foundation for future work.